2012
DOI: 10.1158/1940-6207.capr-11-0555
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of In Vivo Multimodal Optical Imaging for Detection of Oral Neoplasia

Abstract: If detected early, oral cancer is eminently curable. However, survival rates for oral cancer patients remain low, largely due to late stage diagnosis and subsequent difficulty of treatment. To improve clinicians’ ability to detect early disease and to treat advanced cancers, we developed a multi-modal optical imaging system (MMIS) to evaluate tissue in situ, at macroscopic and microscopic scales. The MMIS was used to measure anatomical 100 sites in 30 patients, correctly classifying 98% of pathologically confi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
114
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 34 publications
2
114
0
1
Order By: Relevance
“…Normal squamous epithelium is characterized by regularly spaced, small nuclei. In contrast, the area of HSIL showed larger, more closely spaced nuclei, which is consistent with previous studies using high resolution microendoscopy to study squamous epithelium where increased nuclear density and nuclear size are observed and can be quantified in dysplastic tissue (13,14,31). The DSIMe images corresponding to the HSIL region showed improved image contrast.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Normal squamous epithelium is characterized by regularly spaced, small nuclei. In contrast, the area of HSIL showed larger, more closely spaced nuclei, which is consistent with previous studies using high resolution microendoscopy to study squamous epithelium where increased nuclear density and nuclear size are observed and can be quantified in dysplastic tissue (13,14,31). The DSIMe images corresponding to the HSIL region showed improved image contrast.…”
Section: Resultssupporting
confidence: 90%
“…When used in conjunction with contrast agents, high resolution microendoscopy (HRME) has shown promise to improve early detection of precancerous lesions based on changes in nuclear size, shape, and density (9)(10)(11)(12)(13)(14)(15). However, the coherent fiber optic bundles used in microendoscopes lack inherent optical sectioning capabilities (8); out-of-focus light generated in highly scattering tissues can result in poor image contrast that obscures cellular detail (16,17), which is particularly problematic in tissues with glandular epithelium, such as the breast, where microendoscopic images do not show sufficient contrast to differentiate between normal and neoplastic tissue (18).…”
mentioning
confidence: 99%
“…Identafi TM 3000 technology consists of a small optical fiber that produces various excitation wavelengths and a spectrograph that receives and records on a computer and analyzes, via a dedicated software, the spectra of reflected fluorescence from the tissue. The findings of a more recent study support the ability of noninvasive multimodal optical imaging to accurately identify neoplastic tissue and premalignant lesions (Pierce et al, 2012). This promising technology has an impact on detection and treatment of patients with oral cancer and other epithelial malignancies but further clinical studies are needed.…”
Section: Introductionmentioning
confidence: 69%
“…In 2012, for example, she and her colleagues created a multimodal optical imaging system to noninvasively identify oral cancers and premalignant lesions (10). Three years later her group developed a low-cost, high-resolution microendoscope, and showed that it improves early detection of cancer and precancerous lesions in a variety of organ systems (10).…”
Section: Cancer-detection Innovationsmentioning
confidence: 99%